1984
DOI: 10.1901/jeab.1984.42-143
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Equivalence and Transitive Associations: A Methodological Analysis

Abstract: When a number of two-stimulus relations are established through training within a set of stimuli, other two-stimulus relations often emerge in the same set without direct training. These, termed "transitive stimulus relations," have been demonstrated with a variety of visual and auditory stimuli. The phenomenon has served as a behavioral model for explaining the emergence of rudimentary comprehension and reading skills, and the development of generative syntactic repertoires. This article considers the range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
89
1
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 15 publications
(32 reference statements)
7
89
1
8
Order By: Relevance
“…A emergĂȘncia dos desempenhos em MTS arbitrĂĄrio sĂł foi possĂ­vel porque rf1 estava mutuamente implicado no fortalecimento do responder diante dos estĂ­mulos A1 e B1, enquanto o responder aos estĂ­mulos A2 e B2 era fortalecido por rf2. Dito de outra forma: rf1 era nĂłdulo para A1 e B1, e A2 e B2 tinham rf2 como nĂłdulo (cf., Fields, Verhave, & Fath, 1984).…”
Section: _______________________unclassified
“…A emergĂȘncia dos desempenhos em MTS arbitrĂĄrio sĂł foi possĂ­vel porque rf1 estava mutuamente implicado no fortalecimento do responder diante dos estĂ­mulos A1 e B1, enquanto o responder aos estĂ­mulos A2 e B2 era fortalecido por rf2. Dito de outra forma: rf1 era nĂłdulo para A1 e B1, e A2 e B2 tinham rf2 como nĂłdulo (cf., Fields, Verhave, & Fath, 1984).…”
Section: _______________________unclassified
“…Dn, respectively, to each class. Fields, Verhave, and Fath (1984) showed that to form n-members equivalence classes, it is necessary to teach at least n -1 conditional discriminations. Different training designs may accomplish this, and the number of possible training designs increases with the number of prospective class members.…”
mentioning
confidence: 99%
“…All three types of training structures have been commonly used in the literature to produce two or more equivalence classes 1 (Saunders & Green, 1999). All of these procedures have been regarded as equally likely to produce emergent relations indicative of equivalence classes (e.g., Fields, Verhave, & Fath, 1984;Sidman & Tailby, 1982). The past few years have brought several studies that document differential probability of equivalence class formation following different training structures, both with mentally retarded subjects (Saunders et aI., 1993;Saunders, Wachter, & Spradlin, 1988;Spradlin & Saunders, 1986) and intellectually normal subjects (Arntzen & Holth, 1997;Barnes, 1992, as cited in Barnes, 1994).…”
mentioning
confidence: 99%